2011
DOI: 10.1002/jbm.b.31828
|View full text |Cite
|
Sign up to set email alerts
|

Sea cucumber (Stichopus hermanii) based hydrogel to treat burn wounds in rats

Abstract: Malaysian sea cucumber was incorporated into hydrogel formulation by using electron beam irradiation technique and was introduced as novel cross-linked Gamat Hydrogel dressing. This study investigated whether Gamat Hydrogel enhanced repair of deep partial skin thickness burn wound in rats and its possible mechanism. Wounds were treated with either Gamat Hydrogel, control hydrogel, OpSite V R film dressing or left untreated. Skin samples were taken at 7, 14, 21, and 28 days post burn for histological and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
1
40
0
1
Order By: Relevance
“…Some medicinal agents, such as pharmacological active agents, antibacterial agents, topical anesthetics, bacteriostatic agents and antifungal agents, are often incorporated into the dressings, dependent on the specifi c applications. Many wound dressings made of different materials have been studied and reported, such as hydrocolloid (Jeong et al, 2011), hydrogel (Zohdi et al, 2011), medicated dressings (Yu et al, 2006) and liquid bandages (Martin-Garcia et al, 2005). Klode et al (2011) investigated all kinds of wound dressings, totaling 56 used nowadays, and presented a useful data source that can be used to develop a specifi c wound dressing.…”
Section: Polyurethane For Medical Suppliesmentioning
confidence: 99%
“…Some medicinal agents, such as pharmacological active agents, antibacterial agents, topical anesthetics, bacteriostatic agents and antifungal agents, are often incorporated into the dressings, dependent on the specifi c applications. Many wound dressings made of different materials have been studied and reported, such as hydrocolloid (Jeong et al, 2011), hydrogel (Zohdi et al, 2011), medicated dressings (Yu et al, 2006) and liquid bandages (Martin-Garcia et al, 2005). Klode et al (2011) investigated all kinds of wound dressings, totaling 56 used nowadays, and presented a useful data source that can be used to develop a specifi c wound dressing.…”
Section: Polyurethane For Medical Suppliesmentioning
confidence: 99%
“…Stichopus hermanii can act as anticandidal [8], [9] Stichopus hermanii treated wounds and stimulation tissue regeneration. [10]. The other study show that studies have shown that the extract of Stichopus species also affects viability or proliferation of human fibroblasts and osteoclast cells in a negative manner [10].…”
Section: Introductionmentioning
confidence: 93%
“…infection control, dressing flexibility). [3552] In situ forming gels[38,53–56] and radiation-crosslinked gels[36,44,45,57] are also appealing for the development of novel wound dressings.
Figure 3:Increasing number of research articles concerning the development of hydrogel-based wound dressings, published in the last ten years (Source: PubMed. Keywords: hydrogel wound dressing; burn.
…”
Section: Current and Prospective Use Of Polymeric Hydrogels In Burn Wmentioning
confidence: 99%